Kadar Gula Darah dan Senam Sehat Diabetes Melitus - Rahayu, Dian Yuniar Syanti; Pertami, Sumirah Budi; Budiono, Budiono (Poltekkes Kemenkes Kendari, 2017)
Diabetes mellitus is the second largest non-communicable diseases as hypertension. This study aims to determine the influence of diabetes mellitus exercise decrease blood sugar levels in diabetes mellitus clients. This research is a Quasi-experiment. The population is all patients who visited the health center-Lepo Lepo period January to December 2015 amounted to 374 people and a sample of 12 people, the data obtained using questionnaires and tested using independent t-test. The results showed that the blood sugar levels prior to exercise healthy diabetes mellitus are 12 (100.0%) in the category rose, with average blood sugar levels client is 252 mg / dl. Then the blood sugar levels after doing gymnastics healthy diabetes mellitus most of which 7 (58.3%) in the category down, and 5 (41.7%) in the category rose, with the average blood sugar level, was 220.25 mg client / dl and there is a healthy exercise influence diabetes mellitus to decrease blood sugar levels in diabetes mellitus clients with a value of p = 0.041. Suggestions in this study in order to increase the frequency of diabetes mellitus and healthy exercise examination routine blood sugar checks to clients in order to reduce blood sugar levels of diabetes mellitus alternative therapy.